Media in the Midst of Religion Moderation - Ropingi El Ishaq (IAIN Salatiga, 2021)
Media is an important tool to deliver an information for the public. Communication technology contributes greatly to the dissemination of information in the community. On behalf of freedom of information and democracy, all types of information are scattered in a wide society. It even tends to lose its control. Many ideas carried along with the dissemination of information. Among the ideas that exist are about radicalism and extremism in religion. The wild ideas that developed in the midst of this society pushed the government to rebuild religious thought. Religious moderation is an idea raised by the government to minimize radicalism and extremism. Then how should media regulation be carried out? And how should the media carry out its role within the framework of developing religious moderation? This study was conducted with a normative approach. Standards on how the media should be run and managed become the dominant perspective in this study. Of course, this is intended so that this study cannot be separated from the system applied in democratic politics and existing information. The issue of the role of the media in the midst of democracy and the idea of religious moderation can be explained as follows. First, the needs of information for the society in the era of democracy are pushing to bring more and more widespread information dissemination to a wide audience. This point places the media as an important institution in society. The strategic position of information media in the midst of democratic nature requires the government to be able to formulate media regulations appropriately. So that the media can carry out its role appropriately, namely as a pillar of democracy. Second, Islam is a universal religion that carries the values of humanism and rationalism. For this reason, media professionals must understand Islam's teachings well so that they are not trapped in the spread of information that provokes the emergence of extremism. In the next turn, media practitioners are also expected to be able to respond well to various existing problems, so as to be able to take frames appropriately, neutrally, and educatively, so as not to cause extremism in the community. Furthermore, the idea of religious moderation must also be disseminated by utilizing the media. Whatever the media. So that the idea of religious moderation can be spread, accepted, and carried out by the widest possible audience.